Model Identifkasi Sinyal Jantung Pertama (S1) dan Sinyal Jantung Kedua (S2) pada Janin - Ira Puspasari; Jusak Jusak; Weny Indah Kusumawati; Ekasari Oktarina (Jurnal Rekayasa Elektrika, 2020)
Process of identifying fetal heart sound signals is imperative in recognizing congenital heart function that caused by many factors, such as hereditary factors and food intake of pregnant mothers. This study developed a method for processing heart signals to separate normal fetal phonocardiogram signals from noise by utilizing the Complete Empirical Mode Decomposition (CEEMD) algorithm which is integrated with the Pearson Distance metric. Heart signals that have been separated from noise are then processed using the Shannon Energy equation in order to sharpen the intensity of the first heart signal (S1) and the second heart signal (S2), but at the same time suppress the intensity of the residual noise in the signal. Based on the experiment results from 75 normal fetal heart sound cycles, the model that has been developed is able to identify the S1 signal and S2 signal, the time duration of T11 (S1-S1), and the time duration of T12 (S1-S2). Average duration of T11 and T12 acquired in this research can possibly be used as a reference for measuring the normal duration of fetal heart sound signals.